2009 3rd International Conference on Bioinformatics and Biomedical Engineering 2009
DOI: 10.1109/icbbe.2009.5162213
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Tongue Image Extraction Based on Combination of Color and Space Information

Abstract: Tongue inspection is one of the most important methods of Traditional Chinese Medicine diagnoses. Traditional tongue inspection mainly depends on observations to tongue substance, tongue coating and tongue pattern and diagnostic experience of the doctors. Diagnostic results are restricted by doctor's knowledge level, their experience as well as other subjective factors and affected by the light and temperature of external environment. In order to solve this problem, we should combine Traditional Chinese Medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Zhu et al [ 12 ] introduced a novel approach for color tongue image extraction with fusion of color and space information, which was suggested in a recent authorized China invention patent. This method used multiobjective greedy rules and made fusion of color and space information to extract tongue image.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhu et al [ 12 ] introduced a novel approach for color tongue image extraction with fusion of color and space information, which was suggested in a recent authorized China invention patent. This method used multiobjective greedy rules and made fusion of color and space information to extract tongue image.…”
Section: Methodsmentioning
confidence: 99%
“…Other kinds of methods enriched the application of tongue image extraction. Zhu et al [ 12 ] suggested a kind of color tongue image extraction method which utilized greedy rules with fusion of color and space information in order to extract tongue body region from background accurately. The accuracy of this method was quite high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After successful separation of background from the raw image, the template was found to be effective even for thick tongue coating. It can be useful for the quantitative evaluation of tongue 52 . The hue and intensity were exploited by Jian-Qiang et al, 55 for tongue image segmentation which worked well for regular tongue surfaces, but not for the irregular ones.…”
Section: Image Segmentation and Feature Extractionmentioning
confidence: 99%